2010
DOI: 10.3389/neuro.04.004.2010
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic modulation of intrinsic and synaptic properties of lumbar motoneurons in the neonatal rat spinal cord

Abstract: Although it is known that noradrenaline (NA) powerfully controls spinal motor networks, few data are available regarding the noradrenergic (NAergic) modulation of intrinsic and synaptic properties of neurons in motor networks. Our work explores the cellular basis of NAergic modulation in the rat motor spinal cord. We first show that lumbar motoneurons express the three classes of adrenergic receptors at birth. Using patch-clamp recordings in the newborn rat spinal cord preparation, we characterized the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 50 publications
3
59
0
Order By: Relevance
“…In addition, we found that NA increased sEPSC through α1 receptors in some populations of regular type neurons. Several studies have addressed the relevance of NAergic modulation of synaptic events in the spinal cord (1,2,5,20,29). In this study, α2 receptor-mediated synaptic inhibition of sEPSC was observed in both types of neurons, consistent with previous reports.…”
Section: Synaptic Current Modulation Of Nasupporting
confidence: 80%
See 3 more Smart Citations
“…In addition, we found that NA increased sEPSC through α1 receptors in some populations of regular type neurons. Several studies have addressed the relevance of NAergic modulation of synaptic events in the spinal cord (1,2,5,20,29). In this study, α2 receptor-mediated synaptic inhibition of sEPSC was observed in both types of neurons, consistent with previous reports.…”
Section: Synaptic Current Modulation Of Nasupporting
confidence: 80%
“…Further, we showed α1 receptor-mediated increase of sEPSC. This has also been reported in spinal motor neurons (29) and other supraspinal regions such as the nucleus tractus solitaries (14), paraventricular hypothalamic nucleus (3), and cerebral cortex (17). Comparable to the modulation of sEPSC, inhibition of sIPSC was observed mainly in delayed type neurons, and α1 receptor-mediated enhancement of sIPSC was observed in regular type neurons.…”
Section: Synaptic Current Modulation Of Namentioning
confidence: 75%
See 2 more Smart Citations
“…Spinal cords were fixed in 4% paraformaldehyde in PBS overnight at 4°C, cryoprotected in 20% sucrose, embedded in OCT Tissue-Tek, frozen, and cut transversely on a cryostat (30 M). The slices were mounted on slides and processed for choline acetyl transferase (ChAT) immunodetection using a goat anti-ChAT antibody (1:100; Millipore) revealed with an Alexa Fluor 488 donkey anti-goat secondary antibody (1:500; Tartas et al, 2010). Images of ChAT-immunopositive cells were acquired using a Nikon AZ100M microscope.…”
Section: Methodsmentioning
confidence: 99%